Chapter Integrated Coastal Zone Management of Natura 2000 and cultural heritage sites in Calabrian coastal landscape (Southern Italy) - Cantasano, Nicola (Proceedings e report, 2020)
This study shows the link connecting natural and cultural goods in the coastal landscape of Calabria (Southern Italy), considering seaboard and human impact risk conditions. In fact, Calabria has 58 Natura 2000 sites located on seaboard areas within a length of 300 meters from coast and 63 cultural heritage sites of which 42.9% coincides with the Natura 2000 network. As a results of this paper, the increasing coastal erosion and a heavy human impact have been highlighted as the main hazards to which the natural and cultural goods are exposed, thus it’s necessary a broader approach for the integration of natural and cultural issues into an active Integrated Coastal Zone Management process